Lung adenocarcinoma with clear cell features producing carbohydrate antigen 19-9. (October 2015) - Goto, Taichiro; Hada, Masao; Oyama, Toshio
A 76-year-old man underwent surgery for lung cancer. Histopathologically, most of the resected tumor was composed of polygonal cells with foamy cytoplasm, and the cells were arranged predominantly in acinar patterns. In this case, although the carbohydrate antigen 19-9 level was high before surgery, it normalized after resection. The tumor was considered a carbohydrate antigen 19-9-producing tumor, which was further supported by the results of immunohistochemical analysis. Adenocarcinoma with clear cell features, producing carbohydrate antigen 19-9, is an exceedingly rare entity.